2017
DOI: 10.3390/diseases5010003
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Dietary Intake of Antioxidants and Ocular Disease

Abstract: Abstract:To assess the association between dietary antioxidant intake and the incidence of the three major oxidative stress-related eye diseases, cataracts, glaucoma, and age-related macular degeneration, 78 cases from the University of Auckland Optometry and Vision Science clinic and 149 controls were recruited. Participants completed an antioxidant food-frequency questionnaire, analysed through multiple logistic regression. Protective associations were identified with higher consumption of fruit and vegetabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…The lowest ability to reduce the degree of ferric ion oxidation was found in the 'Hokkaido' (48.57 mM Fe(II)/100 g dm), 'Marina di Chiggia' (58. 19 mM Fe(II)/100 g dm), and 'Green Hubbard' cultivars (66.34 mM Fe(II)/100 g dm). When 80% methanol was used as the solvent, all the cultivars exhibited higher antioxidative activity.…”
Section: Ferric Reducing Antioxidant Power (Frap)mentioning
confidence: 99%
“…The lowest ability to reduce the degree of ferric ion oxidation was found in the 'Hokkaido' (48.57 mM Fe(II)/100 g dm), 'Marina di Chiggia' (58. 19 mM Fe(II)/100 g dm), and 'Green Hubbard' cultivars (66.34 mM Fe(II)/100 g dm). When 80% methanol was used as the solvent, all the cultivars exhibited higher antioxidative activity.…”
Section: Ferric Reducing Antioxidant Power (Frap)mentioning
confidence: 99%
“…Some studies have outlined the potential nutritional or dietary influences on AMD risk [7,[16][17][18][19]. Data emerging from the Age-Related Eye Disease Study (AREDS), advocates a healthy diet with supplementation of zinc, lutein/zeaxanthin and vitamins C and E, as an effective strategy for reducing AMD progression from its early to visually-disabling late stage [16].…”
Section: Introductionmentioning
confidence: 99%
“…A recent case-control study conducted by Braakhuis et al indicated that a higher intake of vitamin C was associated with a reduced risk of oxidative stress-related eye diseases (OR: 0.63; 95% CI, 0.23-1.03; p = 0.022) [46].…”
Section: Vitamins C and Ementioning
confidence: 99%
“…A recent case-control study indicated a protective association between dietary intake of -carotene and oxidative stress-related eye diseases (OR: 0.56; 95% CI, 0.15-0.98; p = 0.007) [46]. However, contradictory results originated from the Blue Mountains Study, which showed a significantly positive correlation between -carotene dietary intake and AMD (R: 1.36; 95% CI, 1.02-1.81 per 1-SD increase; p = 0.039), with a significant trend across increasing tertiles of dietary -carotene intake.…”
Section: -Carotenementioning
confidence: 99%